Representasi Citra Laki-Laki Budaya Sunda: Studi Analisis Semiotik Charles Sanders Peirce dalam Sinetron Preman Pensiun - Utaridah, Nanda (JURNAL SOSIOLOGI, 2015)
Lifting Sunda culture in this Retired Sinetron Freeman become fascination a look on because of setting, dialectal of Ianguage, and comedy situation in its story jell with atmosphere of kesundaan and town of Bandung. Retired Freeman narrate life of group